The Research Trend About Counseling Based on Local Wisdom: A Bibliometric Analysis - Sari, Intan; Afriyati, Vira; Pasmawati, Hermi (BiCED Proceeding, 2023)
This study investigates the development of research trends related to counseling based on local wisdom using a bibliometrics approach, where VOS viewer is used as an analysis tool, and the main data source comes from Scopus. Local wisdom-based Counseling approaches are increasingly becoming the focus of attention in the counseling space, which recognizes the important role of local culture and values in providing effective psychological assistance to Counselors. This research methodology includes the acquisition of data from various sources recorded in the scopus index, then the data is analyzed using the VOS viewer tool to identify research trends, collaboration between researchers, and key concepts that dominate the related literature. The results of this bibliometrics analysis provide in-depth insights into research developments in the domain of local wisdom-based Counseling. Key findings in the study include significant growth in the number of scientific publications focusing on this topic, increased cooperation between researchers with diverse cultural backgrounds, and identification of important concepts such as cultural adaptation in counseling practice, integration of local wisdom in therapeutic approaches, as well as its positive impact on individual and community mental health. The results of this study provide valuable insights for researchers, counseling practitioners, and policymakers to understand the latest developments in counseling research based on local wisdom. This can be the foundation for designing more effective and culturally sensitive approaches to providing psychological support to diverse individuals and communities.